2017
DOI: 10.1080/10409289.2017.1404884
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration Moderates the Association Between Children’s Temperament and Academic Achievement

Abstract: The primary goal of this study was to determine whether sleep duration moderated the relations of two dimensions of children's temperament, shyness and negative emotion, to academic achievement. In the autumn, parents and teachers reported on kindergarteners' and first graders' ( = 103) shyness and negative emotion and research assistants observed negative emotion in the classroom. In the spring, children wore actigraphs that measured their sleep for five consecutive school nights, and they completed the Woodc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 87 publications
(131 reference statements)
0
8
1
Order By: Relevance
“…This study also revealed that father occupation affected the sleep disorder of students. Stress in the job affected the environment of family living, whole family including student have sleep disorder due to stress in the job this result was contrast of other study results [32][33][34] because of our study sample majority of fathers occupation is job compare to business.…”
Section: Discussioncontrasting
confidence: 77%
“…This study also revealed that father occupation affected the sleep disorder of students. Stress in the job affected the environment of family living, whole family including student have sleep disorder due to stress in the job this result was contrast of other study results [32][33][34] because of our study sample majority of fathers occupation is job compare to business.…”
Section: Discussioncontrasting
confidence: 77%
“…Sleep is a fundamental part of development, particularly pertinent in childhood. Research has established the importance of sleep in children relative to biological [ 1 ], neurological [ 2 ], cognitive [ 3 ] and behavioural functioning [ 4 ], academic attainment [ 5 , 6 ] and memory consolidation [ 7 ]. The benefits of good sleep quality and optimal quantity of sleep include, but are not exclusive to, more effective learning and better physical and mental health [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that school-aged adolescents get adequate sleep, school nurses need to be aware of the clinical markers of short sleep duration such as irritability, tiredness when arriving at school, low motivation to engage in class, poor academic achievement, and absence from school (Berger et al, 2018). Moreover, we recommend that parents encourage the establishment of good sleep habits including a consistent sleep schedule.…”
Section: Discussionmentioning
confidence: 99%